Efektivitas pemberian reward dan punishment dalam meningkatkan kedisiplinan shalat fardhu - Anggoro, Muhammad Yogi (Maliki Interdisciplinary Journal, 2024)
Discipline in daily life requires a habit, this needs to be done in the discipline of prayer which can be a means of forming individual personalities to become better individuals, obey time, and be disciplined in their lives. This study aims to improve participants’ discipline in performing the five daily prayers. This study uses a behavior modification approach, specifically by using reward and punishment techniques. This study uses a single case experimental research design (single subject research) with an A-B-A reversal design with data collection carried out through a behavior checklist with Likert scale items of five-time prayer discipline according to Tasmara (1999), namely regarding (1) Punctuality, (2) Responsibility, (3) Willingness and will. The findings of this study show the positive impact of the behavior modification approach, strengthening the score of using rewards and punishments to improve individual discipline in performing prayers. In the baseline (AI), intervention (B), and baseline II (A2) stages, the participant’s discipline level significantly increased in the aspect of punctuality from a score of 6 (A1), 9 (B), to a score of 9.2 (A2), besides that the responsibility aspect received a score of 5.8 (A1), 7.5 (B), to 7.7 (A2), then the aspect of willingness and will reached a score of 4.8 (A1), 8.7 (B), to a score of 9.5 (A2). Initial measurements showed a lack of discipline, but after implementing the intervention, there was a significant increase in discipline scores. Follow-up evaluations showed that participants maintained discipline in performing prayers. Therefore, it can be concluded that the reward and punishment technique effectively improved participants’ discipline in performing the five daily prayers.